Clinical characteristics of infantile cerebral palsy patients with gastrostomy treated in a a specialized health institute in Lima, Peru - Schult Montoya, Sandra Carina (2022)
Introduction: Cerebral palsy is an important disability condition, and the motor disorder is usually accompanied by other comorbidities such as swallowing disorders. Gastrostomy in patients who are unable to feed satisfactorily is an important and increasingly common intervention. Objective: To determine the clinical characteristics of patients with infantile cerebral palsy with gastrostomy treated at the National Institute of Children’s Health between 2013 and 2017. Methods: Case series study of patients diagnosed with PCI with gastrostomy treated at the Children’s Health Institute during 2013 - 2017. Results: 74 patients were included. The average age of gastrostomy placement was 5,8 years, the most frequent indication was swallowing disorder. Spastic type PCI (74,3%) and functional level IV and V (96%) were the main clinical characteristics. Male sex (58,1%), history of preterm delivery (54%) and perinatal etiology (45.9%) were findings like those described in the population with PCI. The average number of outpatient visits was 5,8 times/year, for emergencies 1,8 times/year and for hospitalizations 1,3 times/year. Conclusions: The gastrostomy was placed in patients with a great motor commitment, and high dependency for their activities. The spastic type and perinatal etiology were the most frequent clinical findings. Annual outpatient visits were low on average, which shows that there is still a long way to go to implement multidisciplinary work in this group of patients.